2017
DOI: 10.1002/2017jb014683
|View full text |Cite
|
Sign up to set email alerts
|

Paleointensity From Subaerial Basaltic Glasses From the Second Hawaii Scientific Drilling Project (HSDP2) Core and Implications for Possible Bias in Data From Lava Flow Interiors

Abstract: In this study, we collected samples from subaerial basaltic glassy margins from the second Hawaii Scientific Drilling Project (HSDP2) core. We employed the rigorous “IZZI” method during the paleointensity experiment combined with the stringent “CCRIT” criteria for data selection to obtain 21 robust paleointensity estimates recorded by glassy margins from 20 lava flows. We compared our new results to published paleointensities from the interiors of the lava flows from HSDP2 and found that our data are systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 38 publications
(78 reference statements)
6
22
0
Order By: Relevance
“…(2009), the reasons for the lack of a dipole signal in the global data set are not clear. The results from some experimental protocols may be biased (e.g., Cai et al., 2017; Cromwell et al., 2018). A bias in temporal sampling toward the present could also cause a high bias in the median intensity because more recent data appear to have higher intensities (Constable et al., 2016; Selkin & Tauxe, 2000; Ziegler et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…(2009), the reasons for the lack of a dipole signal in the global data set are not clear. The results from some experimental protocols may be biased (e.g., Cai et al., 2017; Cromwell et al., 2018). A bias in temporal sampling toward the present could also cause a high bias in the median intensity because more recent data appear to have higher intensities (Constable et al., 2016; Selkin & Tauxe, 2000; Ziegler et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, the study was unable to reproduce the high estimates found in Teanby et al (2002) and Laj et al (2011). Cai et al (2017) additionally found systematically lower estimates than Laj et al (2011) using subaerial glassy basaltic margins on older flows from the HSDP2 core, using the same techniques as Cromwell et al (2018). Based on the data herein and the other studies, the thermal OT method appears to give higher PI estimates than other PI methods and is likely an overestimate of the true palaeointensity due to exaggerated multidomain‐like effects and the lack (in these experiments) of any mechanism to detect these.…”
Section: Discussionmentioning
confidence: 93%
“…Hawaiian absolute PIs have substantial temporal coverage and comprise 28% of the global PI (PINT) database in this interval (Biggin et al, 2015) and are therefore important to study to understand long‐term field behavior over this time interval. Numerous studies have taken advantage of the drill core from the Scientific Observation Hole (SOH) and Hawaii Scientific Drilling Project (HSDP) to extract the required PI data over the last 45 kyr (e.g., Cai et al, 2017; Gratton et al, 2005; Teanby et al, 2002), but the data have proven to be inconsistent and thus of potentially limited use.…”
Section: Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous paleointensity study successfully obtained high‐quality paleointensity estimates using submarine basaltic glass as old as 92 Ma (Tauxe & Staudigel, 2004). More recent paleointensity studies on glassy volcanic materials, decades to centuries to tens of thousands of years old, that formed from sub‐aerial and sub‐glacial eruptions have recovered accurate and high‐quality estimates of geomagnetic field strength (Cai et al., 2017; Cromwell et al., 2018; Cromwell, Tauxe, & Halldórsson, 2015; Cromwell, Tauxe, Staudigel, & Ron, 2015). In this study, we conduct IZZI‐modified paleointensity experiments (Tauxe & Staudigel, 2004) on glassy volcanic materials from Aniakchak volcano.…”
Section: Introductionmentioning
confidence: 99%